EFFICACY AND SAFETY OF DULOXETINE IN THE TREATMENT OF CHEMOTHERAPY INDUCED PERIPHERAL NEUROPATHY: A SYSTEMATIC REVIEW AND META-ANALYSIS - Widyadharma, I Putu Eka; Vania Rau, Chiquita Putri; Pinzon, Rizaldy Taslim; Y, Yudiyanta; Indrayani, Agung Wiwiek; Purwata, Thomas Eko; Nugraha, Boya (MNJ (Malang Neurology Journal), 2021)
Background: One of the adverse effects of chemotherapy in the neurological field is chemotherapy-induced peripheral neuropathy (CIPN), it was an adverse effect caused by many chemotherapeutic regimens and a major cause of continuous pain in patients who survived cancer. When the symptoms get worse, survivor’s quality of life is declining and they are often having problems with mental health, insomnia, cognitive functioning, fatigue, physical functioning, and pain. So far the choice of therapy for CIPN is still limited. Now, there was no drug approved to treat pain due to CIPN. Duloxetine are a SNRI (serotonin norepinephrine reuptake inhibitor), which it’s useful in CIPN are highly supported by evidence.Methods: We conducted a systemactic-computer based literature search on January 4, 2019 in PubMed database for article published between 2013 and 2018. We searched for a literature related with used a duloxetine for management of chemotherapy induced peripheral neuropathy.Results: From the 4 studies that included in this review, the total participants are 478 patients with neuropathic pain and already get a chemotherapy regiment. From the meta-analysis showed one study had no effect, two studies had small effect, and one study had medium effect.Conclusion: Duloxetine is a great option for the treatment of CIPN in especially reducing neuropathic pain.